Building Information Modeling (BIM) Implementation Strategy in Construction Service Companies - Dwi Fatkhurohman; Rizqiah Insanita (Quantitative Economics and Management Studies, 2023)
This paper determines and analyzes related to the strategy for implementing Building Information Modeling (BIM) on the Hamawas Toll Road, the General Civil Division (DSU) of PT Hutama Karya (Persero). The background to this strategy was determined by the inhibiting factors for BIM implementation, such as the quality of human resources (HR), implementation methods, and implementation costs. The analysis was carried out using the Analytic Hierarchy Process (AHP) way, which describes complex problems in a multi-level structure to the last level of the alternatives. Level 1 consists of inhibiting factors for BIM implementation. In contrast, level 2 is a sub-criteria of level 1 which consists of work culture, HR capabilities, BIM system implementation, CDE platform utilization, BIM system operating procedures, BIM software, and hardware costs.. The results of the study show that the best strategy based on level 1 is HR quality with a Consistency Ratio (CR) value of 0.02, level 2 is HR capability with a CR value of 0.02, and the alternative is to make BIM legality with a CR value of 0.02. The CR value is less than 0.1, so the data is valid and can be used.